(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper is a theory-drove reasonable record of authoritative change at the interface of further and higher education. It is centered around universities in the further education segment that give courses of higher education regulated by a different higher education part. The examination is worried about the job and capacity of boundary associations and the idea of the exchanges and boundary work that happen between the two parts. It draws upon speculations from political science, economic human science and crafted by anthropologist dissect these cross-division transactions.